UJI EFEK PEMBERIAN EKSTRAK ETANOL 70% BIJI BUAH TERUNG UNGU (SOLANUM MELONGENA L.) TERHADAP KADAR KOLESTEROL HDL SERUM DARAH TIKUS PUTIH JANTAN (RATTUS NORVEGICUS) GALUR WISTAR - Fajriyatun, Baiq Nova; Sutrisna, EM; Nirlawati, Dona Dewi (Biomedika, 2014)
Extract of eggplant fruit (Solanum melongena L.) seed is a plant that has anti-hypercholesterolemia effect on the state of dyslipidemia. One of the compounds contained in them are fl avonoids nasunin which can increase levels of HDL cholesterol (high density lipoprotein). HDL cholesterol is considered as a compound have the ability to remove excess cholesterol from the arteries, and therefore called good cholesterol. This study is a laboratory experimental research using pretest and posttest control group. The sample consisted of 25 rats were divided into 5 groups. Group I is a negative control (-), Group II is a positive control (+), group III was treated 1 (dose 1), group IV was treated 2 (dose 2), and V is the treatment group 3 (dose 3). Each group was given a high-cholesterol diet. Negative and positive control group were not given the extract of fruit seed of eggplant, the treatment groups III, IV, and V were given the extract of fruit seed of eggplant with each dose of 20 mg/kg, 40 mg/kg, 80 mg/kg were given for 4 weeks. HDL cholesterol levels will be measured before and after cholesterol diet and calculated each week after giving of the extract. The data obtained tested with statistical tests One-Way Anova. HDL cholesterol positive control group and the treatment group showed signifi cant differences between groups. Treatment groups 1 and 2 levels of HDL cholesterol lower than the positive control group and the treatment group 3. Extract of eggplant fruit seed dose of 80 mg/kg show an increase in HDL cholesterol levels were signifi cantly (p <0.05). The 70% ethanol extract of eggplant fruit seed at a dose of 80 mg/kg can increase HDL cholesterol levels signifi cantly.Keywords : extract of eggplant fruit seed, hypercholesterol, HDL cholesterol